Bioactive oxynitride glasses: Synthesis, structure and properties. Issue 12 (September 2016) - Bachar, Ahmed; Mercier, Cyrille; Tricoteaux, Arnaud; Leriche, Anne; Follet, Claudine; Hampshire, Stuart
Abstract: The low mechanical strength of bioactive glasses restricts their use to non load-bearing applications. One way to increase strength of glasses is to introduce nitrogen into the silicate network. Oxynitride bioactive glasses in the SiO2 –CaO–Na2 O–Si3 N4 system were successfully prepared. Structural characterization using 29 Si MAS-NMR shows that, as nitrogen is substituted for oxygen, formation of [SiO3 N] tetrahedra and Q 4 units occurs with extra bridging anions at the expense of Q 3 units. Glass transition temperature, hardness, Young's modulus and fracture resistance increase with nitrogen content because of the extra cross-linking of the glass network. CaF2 was substituted for CaO in these glasses which results in decreases in glass transition temperature. Thus, glasses can be melted at lower temperatures while addition of fluorine allows higher solubility of nitrogen and has no effect on the significant increases in mechanical properties induced by nitrogen substitution. Initial assessment of bioactivity suggests that varying the N content may allow tailoring of the level of bioactivity of these glasses.